Impact of Covid-19 Pandemic upon Iraqi women’s Sexual and Reproductive Health at Primary Health Care Centers - Ghafel, Hawraa Hussein (Journal of Contemporary Medical Sciences, 2023)
Objectives: The aim of this study was to assess the repercussions of the COVID-19 pandemic on the sexual and reproductive well-being of women. Methods: Employing a descriptive design with a correlational approach, the study was conducted between November 2021 and July 2022. The sample consisted of (180) women within the reproductive age range of 17 to 49 years. This non-probability 'purposive sample' was chosen deliberately. Data analysis was conducted using descriptive and correlational statistics. Results: The investigation divulged significant findings. A considerable proportion of women (55.6%) reported being unable to access contraception during the pandemic. Moreover, (45%) experienced unintended pregnancies amid the pandemic. Additionally, concerns linked to the pandemic led to a lack of follow-up visits for (73.3%) of participants. The study also highlighted the distressing issue of domestic violence during COVID-19: Over half of the women (51.1%) reported exposure to domestic violence, attributing it to prolonged periods of their husbands staying at home. Furthermore, (51.7%) noted an escalation in domestic violence, and (38.3%) revealed that their husbands showed inadequate concern for their sexual well-being. Conclusion: The COVID-19 pandemic detrimentally affected the sexual and reproductive health of women, manifested through challenges encountered during pregnancy, childbirth, postpartum phases, and family planning. Furthermore, a significant proportion of women faced an increased risk of domestic violence due to the pandemic and the extended presence of their husbands at home.